Uterine rupture after previous caesarean section with hysterotomy above the lower uterine segment: Prelabour uterine rupture and placenta previa - Dellino, Miriam; Crupano, Francesco Maria; He , Xuemin; Malvasi, Antonio; Vimercati, Antonella (Acta Biomedica Atenei Parmensis, 2022)
ABSTRACT Background Spontaneous uterine rupture is a severe pregnancy complication. Several risk factors have been described, especially for women with a previous caesarean section. Method We reported two cases of uterine rupture (UR) occurring outside of labour in patients with a history of caesarean section (CS) due to placenta previa. Results: The current study evaluates how a higher hysterotomy, combined with some risk factors, can increase the prevalence of UR in the subsequent pregnancy. Conclusion This study supports that a careful evaluation of risk factors can identify patients who need a specific follow up to early diagnose and treat UR and thus improve the maternal-fetal outcome.